1985
DOI: 10.1007/bf02798546
|View full text |Cite
|
Sign up to set email alerts
|

Surface modification of proteins activation of monomethoxy-polyethylene glycols by phenylchloroformates and modification of ribonuclease and superoxide dismutase

Abstract: A single-step method of activation of monomethoxypolyethylene glycols suitable for its binding to polypeptides and proteins is proposed. Based on the reaction with 2,4,5-trichlorophenylchloroformate or p-nitrophenylchloroformate, it gives reactive PEG-phenylcarbonate derivatives. The PEG intermediate is stable on storage, the activating group is easily quantified,and the reaction with amino acid and proteins proceeds rapidly at pH near neutrality. The PEG derivatization of enzymes with this procedure is less i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(67 citation statements)
references
References 14 publications
1
61
0
1
Order By: Relevance
“…While these results are consistent with decreased CTL, it suggests that there may be a switch in the qualitative nature of the B-cell response from Th1 to Th2 dependent. There have been documented toxicities associated with PEGs activated by cyanuric chloride in which the triazine rings of the activating group stimulate Th2 responses (9,49). This type of response could account for the failure of the PEGylated viruses to produce significant levels of gene expression in animals immunized with the same modified virus (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…While these results are consistent with decreased CTL, it suggests that there may be a switch in the qualitative nature of the B-cell response from Th1 to Th2 dependent. There have been documented toxicities associated with PEGs activated by cyanuric chloride in which the triazine rings of the activating group stimulate Th2 responses (9,49). This type of response could account for the failure of the PEGylated viruses to produce significant levels of gene expression in animals immunized with the same modified virus (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…When comparing various conjugation ratios using 2, 5, 10, 12 and 20 kDa polymers linked to either primary amines or carboxylic acids, Lee et al found that an increase in polymer length was found to be more effective for extending serum halflife than using a corresponding increase in total PEG by using smaller polymer lengths at a higher conjugation ratio (Lee et al 1999). These studies agree Reactivity & Characteristics PEG Carbonyl-Imidazole (Beauchamp et al, 1983;Veronese et al, 1985) N-terminal α-amines and lysine ε-amine group acylation leading to formation of carbamate linkages.…”
Section: Conjugates With Hydrophilic Polymersmentioning
confidence: 80%
“…This as well as the toxicity of the derivative and its promiscuous reactivity with the side chains of Cys and Tyr (Zalipsky et al, 1992) provided the impetus for the discovery of new chemistries of PEG denvatization. (Beauchamp et al, 1983) and MPEGphenylcarbonate (Veronese et al, 1985) were less promiscuous than the cyanuric chloriâe derivative, but suffered ffom poor reactivity and reagent toxicity, respectively. MPEG-succinirnidyl succinate (Abuchowski et al, 1984) and MPEG-succinimidyl carbonate (Zalipsky et al, 1992) exhibit high reactivity and specificity.…”
Section: Chemistries Of Peg Derivatizationmentioning
confidence: 99%